1867 Miss. Laws 327-28 - (:unkn) unknown (My University, 1867)
Ch. 249, § 1:[A] tax of not less than five dollars or more than fifteen dollars shall be levied and assessed annually by the board of Police of Washington county upon every gun and pistol which may be in the possession of any person in said county,
Keywords: TAX - PROPERTY OR SALES